2007
DOI: 10.1021/bi701000k
|View full text |Cite
|
Sign up to set email alerts
|

NMR Study of the Inhibition of Pepsin by Glyoxal Inhibitors:  Mechanism of Tetrahedral Intermediate Stabilization by the Aspartyl Proteases

Abstract: Z-Ala-Ala-Phe-glyoxal (where Z is benzyloxycarbonyl) has been shown to be a competitive inhibitor of pepsin with a Ki = 89 +/- 24 nM at pH 2.0 and 25 degrees C. Both the ketone carbon (R13COCHO) and the aldehyde carbon (RCO13CHO) of the glyoxal group of Z-Ala-Ala-Phe-glyoxal have been 13C-enriched. Using 13C NMR, it has been shown that when the inhibitor is bound to pepsin, the glyoxal keto and aldehyde carbons give signals at 98.8 and 90.9 ppm, respectively. This demonstrates that pepsin binds and preferentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
2

Year Published

2009
2009
2014
2014

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 54 publications
0
8
0
2
Order By: Relevance
“…However, if the glyoxal group was coordinated to the zinc atom we would expect the glyoxal hemiacetal hydroxyl groups to also be ionised with the hemiacetal carbon having a chemical shift of ~97 ppm which is not observed. We have also shown that when a glyoxal inhibitor binds to pepsin there is an increase in chemical shift of the glyoxal hemiacetal carbon from 89.8 to 90.9 even though both the hemiacetal and hemiketal hydroxyl groups are not ionised in the free and bound glyoxal [9]. The increase in chemical shift of the glyoxal hemiacetal carbon from 90.4 to 92.0 ppm on binding the UK-370106-CO 13 CHO inhibitor to SCD is similar in magnitude and can be attributed to the difference in the environment of the free and bound species.…”
Section: Discussionmentioning
confidence: 69%
See 3 more Smart Citations
“…However, if the glyoxal group was coordinated to the zinc atom we would expect the glyoxal hemiacetal hydroxyl groups to also be ionised with the hemiacetal carbon having a chemical shift of ~97 ppm which is not observed. We have also shown that when a glyoxal inhibitor binds to pepsin there is an increase in chemical shift of the glyoxal hemiacetal carbon from 89.8 to 90.9 even though both the hemiacetal and hemiketal hydroxyl groups are not ionised in the free and bound glyoxal [9]. The increase in chemical shift of the glyoxal hemiacetal carbon from 90.4 to 92.0 ppm on binding the UK-370106-CO 13 CHO inhibitor to SCD is similar in magnitude and can be attributed to the difference in the environment of the free and bound species.…”
Section: Discussionmentioning
confidence: 69%
“…However, it is surprising that with the aspartyl protease pepsin [9] and with the metalloprotease SCD the association rate constant of glyoxal inhibitors is also at least a 50 x slower than the diffusion controlled rate constant. Hydration and dehydration of carbonyl groups is a slow process [39].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Z-Ala-Ala-Phe-H (Scheme 1A) was synthesized as described by Petrillo et al [4]. Z-Ala-Ala-Phe-13 COOCH 3 and Z-Ala-Ala-Phe-13 COCHO (Scheme 1D) were synthesized as described by Cosgrove et al, [18].…”
Section: Synthesis Of Z-ala-ala-phe-h Z-ala-ala-phe-cooch 3 and Z-almentioning
confidence: 99%